2020
DOI: 10.1371/journal.pone.0243154
|View full text |Cite
|
Sign up to set email alerts
|

NIRS-based monitoring of kidney graft perfusion

Abstract: Introduction Acute early vascular complications are rare, but serious complications after kidney transplantation. They often result in graft loss. For this reason, shortening the diagnostic process is crucial. Currently, it is standard procedure to monitor renal graft perfusion using Doppler ultrasound (DU). With respect to acute vascular complications, the main disadvantage of this type of examination is its periodicity. It would be of great benefit if graft blood perfusion could be monitored continuously dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…This might be considered too invasive, especially in the paediatric population, and might not be free from complications, even if no adverse events were reported during this procedure. 17 Further investigation should also relate rSrO2 to perfusion renal scintigraphy. Even if this is a point-evaluation of allograft perfusion, this is the most objective modality to assess both kidney vascularisation and function, also adding information about the early prognosis of the KT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This might be considered too invasive, especially in the paediatric population, and might not be free from complications, even if no adverse events were reported during this procedure. 17 Further investigation should also relate rSrO2 to perfusion renal scintigraphy. Even if this is a point-evaluation of allograft perfusion, this is the most objective modality to assess both kidney vascularisation and function, also adding information about the early prognosis of the KT.…”
Section: Discussionmentioning
confidence: 99%
“…However, the main concern about this tool involves the need for a second intervention for its removal. This might be considered too invasive, especially in the paediatric population, and might not be free from complications, even if no adverse events were reported during this procedure 17 …”
Section: Discussionmentioning
confidence: 99%
“…Efforts focus on experimental and clinical studies analyzing the uterine vasculature in preparation of uterus transplantation, 12,13 and the collection and examination of adipose tissue from living kidney donors utilized for research of atherosclerosis. 14 Preclinical research includes monitoring of kidney graft perfusion, 15 compromised wound healing in diabetes, 16 and tissue engineering of vascular grafts. 17…”
Section: Researchmentioning
confidence: 99%
“…22 The latest experimental work involving NIRS as RG perfusion monitoring by Maly et al demonstrated the feasibility and reproducibility with 100% sensitivity of NIRS for renal transplant perfusion monitoring in swine renal auto-transplantation experimental model when detecting a decreasing RG perfusion. 23…”
Section: Reviewmentioning
confidence: 99%